Good regulations, bad regulation: a Peruvian port case - Defilippi, Enzo (2012)
Lead poisoning of Callao’s population is the most severe externality port operations cause in Peru. The problem could have been tackled in 2009, after the government issued a decree regulating how mineral ore was to be handled at Peruvian ports. However, the port regulator’s inability to follow the criteria contained in their own regulations led the procedure of selecting the providers of the service to continuous delays, and finally, to a complete stop. As a consequence, Callao’s population will continue to be affected by this externality until 2013. The problem the regulator could not solve was to determine whether the market for ‘mineral ore stevedore services’ at Callao Port was monopolistic or competitive. This article re-examines the case and concludes that the market for the service has natural monopoly characteristics. Therefore, the regulator should have ordered the call of an auction to select the least-expensive provider and thus, spare the population from four more years of lead poisoning.